Організаційні аспекти забезпечення економічної безпеки підприємства - Журавель, М. Ю.; Стороженко, О. В. (ХНУРЭ, 2014)
Key objectives to ensuring enterprise economic security to its functional components are proposed. The approach to economic security medium enterprises in Ukraine is Substantiated. This approach is based to the maximum delegation of authority of ensuring the economic security to the existing structural units
Keywords: економічна безпека; безпека підприємства